Evaluating comparative b-glucan production aptitude of Saccharomyces cerevisiae, Aspergillus oryzae, Xanthomonas campestris, and Bacillus natto - Gemilang Lara Utama; Casey Dio; Joko Sulistiyo; Chye, Fook Yee; Elazmanawati Lembong; Yana Cahyana; Deepak Kumar Verma; Mamta Thakur; Ami R. Patel; Smita Singh (Elsevier, 2021)
b-glucan is a natural polysaccharide derivative composed of a group of glucose monomers with b-glycoside bonds that can be synthesized intra- or extra-cellular by various microorganisms such as yeasts, bacteria, and moulds. The study aimed to discover the potential of various microorganisms such as Saccharomyces cerevisiae, Aspergillus oryzae, Xanthomonas campestris, and Bacillus natto in producing b-glucan. The experimental method used and the data were analyzed descriptively. The four microorganisms above were cultured under a submerged state in Yeast glucose (YG) broth for 120 h at 30 C with 200 rpm agitation. During the growth, several parameters were examined including total population by optical density, the pH, and glucose contents of growth media. b-glucan was extracted using acid-alkaline methods from the growth media then the weight was measured. The results showed that S. cerevisiae, A. oryzae X. campestris, and B. natto were prospective for b-glucans production in submerged fermentation up to 120 h. The highest b-glucans yield was shown by B. natto (20.38%) with the b-glucans mass of 1.345 ± 0.08 mg and globular diameter of 600 lm. The highest b-glucan mass was achieved by A. oryzae of 82.5 ± 0.03 mg with the total population in optical density of 0.1246, a final glucose level of 769 ppm, the pH of 6.67, and yield of 13.97% with a globular diameter of 1400 lm.